The Effect of Online Stores on the Sustainability of Vegetable Traders in Traditional Markets - Prayoga, Rico Dayu Dwi; Relawati, Rahayu; Amir, Nur Ocvanny (Jurnal Dinamika Sosial Ekonomi, 2025)
Plumpang Market is the largest village market in the sub-district due to its location near the main road connecting Tuban and Bojonegoro Districts. Over the past decade, online market competition has emerged. This study aims to analyze the differences in average: revenue, costs, and income, as well as to identify which types of vegetables were most affected before and after the introduction of online shops. The research location is the traditional market in Plumpang Village, Plumpang District, Tuban Regency. The analysis method used is quantitative with Paired Sample t test and descriptive quantitative presented in graph. The results show that after the advent of online shops, revenue decreased, costs increased, and income fell. Some vegetables have seen a decline in demand as consumers shop online, such as chilies, long beans, tomatoes, and others. There are also vegetables that have experienced an increase in demand, which is experienced by traditional market vegetable traders who also sell online. The emergence of online shops causes the Plumpang Market to become quiet, and can reduce the revenue and income of vegetable traders. The decline in revenue and income of vegetable traders in Plumpang Market is because some consumers have begun to switch to shopping for vegetables to online shops. Their perception of online shops is more practical and efficient.